Działalność polityczna księcia Adama Jerzego Czartoryskiego wobec Wielkiej Brytanii w sprawie belgijskiej (1838-1839) - Żurawski vel Grajewski, Radosław (Acta Universitatis Lodziensis. Folia Historica, 1999)
The „diplomacy” in exile leaded by prince Adam Czartoryski took an active part in the second Belgian crisis in the years 1838-1839. The policy of Czartoryski towards that question was partly a continuation of that one of the period of the first Belgian crisis of 1830-1833. However in 1838 he was conscious that in fact there was no hope to expect a war over Belgium. From the Polish point of view, as usually, only a great military contest in Europe could create a situation in which Poland would be restored and it was the main aim of the Polish political activity in exile. Czartoryski tried to exploit the crisis mainly to promote the Polish cause in the European policy and public opinion. During his conversation with British statesmen he demanded to solve the Polish question on the conference of ambassadors – just as it had been done with the Belgian one. He participated in political rupture between Austria, Prussia and Belgium in 1839 connected with the question of general Jan Skrzynecki – former Polish commander in chief during November Uprising in 1831, who came to Brussels to join the Belgian army. Czartoryski obtained the support of British diplomacy for general Skrzynecki, and others Polish officers in Belgium. But Foreign Office was interested in the peaceful and quick end of crisis. London hoped to collaborate with Vienna over Eastern Question where a political tension rapidly grew in 1839. Quarrel in Belgium still created some difficulties in that collaborations in Near East and Turkey. In that situation Czartoryski could not expect a war in Europe over Belgium but he tried to convince Palmerston – British Foreign Secretary – that the attitude of Austria towards Poland is the best criterion of her loyalty towards the future Austro-British alliance and that Foreign Office should press Metternich to resign from his oppressive policy in that country. According to him, if Vienna was not able to change her policy towards the Poles as she showed in the question of Polish soldiers in Belgium, it would mean that Austria was still closely connected with Russia – the main British enemy in Near East and Central Asia.